Serum Tumor Markers in Paraneoplastic Neurologic Syndromes: A Systematic Review of Guidelines - Trevisiol, Chiara; Cani, Ilaria; Fabricio, Aline S. C.; Gion, Massimo; Giometto, Bruno; De Massis, Patrizia (Frontiers in Neurology, 2021)
Purpose: Algorithms for the detection of a malignancy in patients with unclear neurologic symptoms suspicious for paraneoplastic origins, are not universally applied. Frequently, circulating tumor markers (TMs) are considered a valuable tool for cancer diagnosis in patients with paraneoplastic neurologic syndromes (PNS). Our aim was to extract from clinical practice guidelines the recommendations on the use of TMs and onconeural antibodies (Abs) for the diagnosis of malignancies in PNS and put them in evidence in a common framework to facilitate diffusion, dissemination and implementation. Methods: Systematic literature searches for guidelines on both oncology and PNS published since 2007 were performed. Guidelines containing information and recommendations for clinical practice pertaining to screening and diagnosis of PNS were selected. Information on circulating TMs and onconeural Abs was extracted and synthesized in consecutive steps of increasing simplification. Results: We retrieved 799 guidelines on oncology as eligible for the potential presence of information on PNS but only 6 treated diagnosis or screening of cancer in PNS and were selected. Seventy-nine potentially relevant guidelines on PNS were identified as eligible and 15 were selected. Synoptic tables were prepared showing that classical TMs are not recommended for the screening or the diagnosis of a malignancy in patients with a suspected PNS. Neither onconeural Abs should be considered to screen the presence of a malignancy, although they could be helpful to define the probability of the paraneoplastic origin of a neurologic disorder. Conclusion: The present work of synthesis may be an useful tool in the process of diffusion, dissemination and implementation of guidelines recommendations, potentially facilitating the decrease of inappropriate use of circulating biomarkers for cancer screening in the presence of PNS.